Indication of ACE-inhibitors post-myocardial infarction - Ertl, G; Gaudron, P; Neubauer, S; Hu, K; Zdrojewski, T; Horn, M; Kochsiek, K (1994)
Prognosis of patients post-myocardial infarction depends largely on the degree of left ventricular dysfunction, which results from loss of contractile tissue and remodeling of infarcted and surviving myocardium. This remodeling process may result in chronically progressive dysfunction and ultimately in heart failure. Next to mechanical determinants humoral control of hypertrophy, dilatation and qualitative changes of surviving myocardium are discussed. A major determinant of the extent of remodeling is infarct size. Efficacy of angiotensin-converting enzyme (ACE) inhibitors on infarct size was tested in animal experiments with conflicting results. Recent clinical studies also report beneficial (GISSI-3 and ISIS-4) or no (CONSENSUS II) effects on survival post-myocardial infarction when ACE-inhibitors were used in the acute phase. Up to date it remains unsettled which patients may benefit from acute therapy with ACE-inhibitors. Three days after myocardial infarction hemodynamically stable patients with heart failure may be treated with ACE-inhibitors (AIRE study). Prognosis may be improved and manifestation of heart failure prevented or delayed also in patients without heart failure treated in this phase of myocardial infarction with ACE-inhibitors (SAVE study). Prevention of heart failure may also be observed in patients treated later (at least 4 weeks) after myocardial infarction (SOLVD prevention arm). It is essential for this indication that patients are carefully selected for treatment depending on left ventricular function. Duration of treatment in patients with severe left ventricular dysfunction probably has to be lifelong, the doses of ACE-inhibitors used have to be relatively high (e.g. 3 x 50 mg captopril or 2 x 10 mg enalapril). It remains unsettled, whether or not lower doses are effective. It also remains unclear whether or not other drugs like nitrates may have similar effects. The combination of ACE-inhibitors with β-receptorblockers, thrombolytic therapy and aspirin, respectively, did not prevent the effects of the ACE-inhibitor in the SAVE-study.